ANALISIS KINERJA KEUANGAN PT. BANK CENTRAL ASIA SYARIAH DI INDONESIA PERIODE 2015-2024 DENGAN MENERAPKAN METODE DU PONT SYSTEM - WAHYUNI; ROSMALA DEWI; ERFIN MARDALENA; DARMAN SYAFE’I; NOVIE AL MUHARIAH (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to analyze the financial performance of PT. Bank Central Asia Syariah in Indonesia for the period 2015-2024 by applying the Du Pont System method. Financial performance is an important indicator for assessing a bank's ability to manage resources and generate profits effectively and efficiently. The Du Pont System method was chosen because it provides a comprehensive overview of financial performance through profitability and activity ratios. The variables analyzed include Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Investment (ROI). The results show that the NPM value during the research period tended to increase and in several year entered the healthy category, indicating the bank's improving ability to generate net profit from income. The TATO value was in the very healthy category, but showed a downward trend, indicating a slowdown in the effective utilization of assets. Meanwhile, the ROI value tended to increase, but overal it was still in the fairly healthy category. This shows that although BCA Syariah's financial performance has experienced positive developments, the bank still needs to improve operational efficiency and asset optimization in order to drive more sustainable profitability. The results of this study are expected to serve as evaluation material for bank management and a reference for further research.